2017
DOI: 10.1021/acs.jpca.6b12938
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Mechanism of Perchlorinated Cyclopentasilane (Si5Cl10) Ring Flattening in the [Si5Cl10·2Cl]2– Dianion

Abstract: We report the detailed computational study of flattening of the puckered Si ring by suppression of the pseudo-Jahn-Teller (PJT) effect through coordination of two Cl anions to the molecule forming an inverse sandwich dianion [SiCl·2Cl] complex. The PJT effect that causes nonplanarity of the SiCl structure (C) results from vibronic coupling of pairs of occupied molecular orbitals (OMOs) and unoccupied molecular orbitals (UMOs). It was shown that filling the intervenient molecular orbitals of puckered SiCl with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Most key structural parameters of [Si 5 Cl 10 · 2Cl] 2– have been correctly predicted by a recent DFT study . The most significant deviation between the computed and experimentally determined values is evident for the Cl – ··· Cl – distance (calcd: 4.215 Å vs. exp: 4.292 Å).…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Most key structural parameters of [Si 5 Cl 10 · 2Cl] 2– have been correctly predicted by a recent DFT study . The most significant deviation between the computed and experimentally determined values is evident for the Cl – ··· Cl – distance (calcd: 4.215 Å vs. exp: 4.292 Å).…”
Section: Resultsmentioning
confidence: 60%
“…Nevertheless, also the DFT calculations unequivocally confirm much farther separated Cl – ions in the Si 5 compared to the Si 6 diadduct. To rationalize the planar conformation of the Si 5 ring in [Si 5 Cl 10 · 2Cl] 2– , the authors offer a similar explanation as previously discussed for the [Si 6 X 12 · 2 X ] 2– diadducts …”
Section: Resultsmentioning
confidence: 61%
“…In fact, crystallographic studies [ 35 , 36 , 37 ] have shown that perhalogenated cyclohexasilanes can strongly bind electron-rich moieties, such as halide anions or organocyanides (such as acetonitrile). Several theoretical studies [ 38 , 39 , 40 , 41 ] have explored this possibility by theoretically analyzing a series of anion/lone pair-Si inverted sandwiched complexes and confirming their ability to behave as efficient ditopic anion receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Another common property characteristic of both halogenated cyclosilanes is Si 6 (or Si 5 ) ring flattening upon donors’ coordination that was also observed in charged complexes as well as in the neutral ones. The suppression of ring puckering effect as well as the origin of Si hyper-coordination in chlorinated cyclic silanes has been extensively studied. Using density functional theory (DFT) methodology it was shown that for both chlorinated CPS and CHS the Si ring distortion is presumably a consequence of pseudo-Jahn–Teller (PJT) effect that occurs due to a vibronic coupling between pairs of occupied (OMOs) and unoccupied molecular orbitals (UMOs).…”
Section: Introductionmentioning
confidence: 99%
“…One of the strongest arguments in favor of PJT effect-driven Si-ring puckering in halogenated cyclosilanes is a possibility of its suppression by coordination of two donor ions (e.g., F, Cl, Br, and I anions) below and above the midring. Thus the DFT modeling has also shown that filling the Si 5 Cl 10 and Si 6 Cl 12 UMOs engaged in vibronic coupling with electron pairs of Cl – donors upon coordination enables complete suppression of the PJT effect (experimentally observed flattening of Si 6 ring) and formation of inverse sandwich compounds. , It was presumed that the formation of the Lewis acid site in the middle of Si 6 ring, on which the apical donors’ electrons are partially accommodated, occurs due to withdrawal of a significant portion of electron density from the Si atoms of the ring by 12 halogens. , …”
Section: Introductionmentioning
confidence: 99%